Disruption of TWIST1 translation by 5′ UTR variants in Saethre‐Chotzen syndrome. Issue 10 (7th August 2018) - Zhou, Yan; Koelling, Nils; Fenwick, Aimée L.; McGowan, Simon J.; Calpena, Eduardo; Wall, Steven A.; Smithson, Sarah F.; Wilkie, Andrew O.M.; Twigg, Stephen R.F.
Abstract: Saethre‐Chotzen syndrome (SCS), one of the most common forms of syndromic craniosynostosis (premature fusion of the cranial sutures), results from haploinsufficiency of TWIST1, caused by deletions of the entire gene or loss‐of‐function variants within the coding region. To determine whether non‐coding variants also contribute to SCS, we screened 14 genetically undiagnosed SCS patients using targeted capture sequencing, and identified novel single nucleotide variants (SNVs) in the 5′ untranslated region (UTR) of TWIST1 in two unrelated SCS cases. We show experimentally that these variants, which create translation start sites in the TWIST1 leader sequence, reduce translation from the main open reading frame (mORF). This is the first demonstration that non‐coding SNVs of TWIST1 can cause SCS, and highlights the importance of screening the 5′ UTR in clinically diagnosed SCS patients without a coding mutation. Similar 5′ UTR variants, particularly of haploinsufficient genes, may represent an under‐ascertained cause of monogenic disease. Abstract : Saethre‐Chotzen syndrome (SCS) is caused by haploinsufficiency of the transcription factor TWIST1. We describe novel pathogenic variants (c.‐263C>A and c.‐255G>A) within the upstream non‐coding sequence of TWIST1 in two families with SSCS. These variants create new translation start sites (upstream AUGs) that we show through luciferase assays are likely to interfere with translation of the main TWIST1 open reading frame.